2022
DOI: 10.1186/s12913-022-08670-3
|View full text |Cite
|
Sign up to set email alerts
|

Professional wellbeing and turnover intention among child therapists: a comparison between therapists trained and untrained in Trauma-Focused Cognitive Behavioral Therapy

Abstract: Background Poor professional wellbeing and job turnover is challenging for child mental health clinics and despite an increasing interest in implementing evidence-based practices (EBPs) in mental health services, little is known about if and how using EBPs may influence therapists’ professional wellbeing and turnover intention. To investigate this, we compare the average level of compassion satisfaction, burnout, secondary traumatic stress, and turnover intention between therapists trained in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…These results are important because there are thousands of previously trained TF-CBT clinicians (Heck et al, 2015; Sigel et al, 2013) who might benefit from the use of the PRACTICE self-care skills taught in this course. In fact, recent research has indicated that over 70% of TF-CBT-trained clinicians surveyed reported medium to high levels of STS and burnout (Aminihajibashi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are important because there are thousands of previously trained TF-CBT clinicians (Heck et al, 2015; Sigel et al, 2013) who might benefit from the use of the PRACTICE self-care skills taught in this course. In fact, recent research has indicated that over 70% of TF-CBT-trained clinicians surveyed reported medium to high levels of STS and burnout (Aminihajibashi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The shorter duration of the standalone PMP self-care course (i.e., 2 months) examined here as compared to a learning collaborative (i.e., 9 months) as well as the less intensive PMP format (i.e., course sessions for 1 hr once per week vs. multiple training days and 16 1-hr consultation calls) may be more attractive to stressed and overwhelmed clinicians given the reduced time commitment. Although recent research indicates that being trained in TF-CBT alone may serve as a protective factor against burnout (Aminihajibashi et al, 2022), it may not offer protective benefits against STS over time given the stress of the field. The more succinct and accessible format of the six-session virtual self-care course may also lead to a greater number of clinicians being able to participate in and benefit from the course, which may help with directly addressing STS symptoms and feelings of burnout among professionals working with trauma-exposed clients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to professionals from other healthcare sectors, mental health professionals report poorer well-being ( 1 ), and high rates of both burnout ( 2 , 3 ) and secondary traumatic stress ( 4 , 5 ). At the same time, they also express a high level of compassion satisfaction [( 6 , 7 ); see section 2.2 for definition of these concepts]. Particularly working with traumatized and mentally distressed children has been reported to be emotionally more demanding than working with adults ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%